Acceptability and Feasibility of the Plasma Separation Card for an Integrated Model of Care for HBV and HCV Screening Among People Attending HIV Clinics in Cameroon and Uganda - Camila A Picchio; Aina Nicolàs; Ironne Valdèse Ayemfouo Fofou; Viola Kasone; Magellan Guewo-Fokeng; Claude T Tagny; Teddy Nanyonjo; Hellen Nansumba; Yves Nacel Kouongni; Rita Gaëlle Epse Sezawo Kamdjeu; Emmanuel Seremba; Charles Kouanfack; et al. (Springer, 2024)
Abstract Background Sub-Saharan African countries have a high burden of viral hepatitis and poor access to screening and care. The aim of this study was to evaluate the feasibility and acceptability of using the plasma separation card (PSC) for viral hepatitis B and C screening among people living with HIV (PLHIV) in Cameroon and Uganda. Methods This is a cross-sectional study carried out between 05/2021 and 03/2023 including 192 PLHIV in Cameroon (n = 104) and Uganda (n = 88). Basic sociodemographic variables and whole blood samples were collected. Adequate filling with blood of PSCs was used to determine feasibility together with participant responses to questions on acceptability. A logistic regression model was carried out to assess the relationship between PSC acceptability and factors of interest. Results 70% of participants reported PSC as an acceptable viral hepatitis screening tool, and it was significantly more accepted in Uganda than Cameroon (100% vs. 43.2%, p < 0.001). Similarly, 75% of PSCs had at least one spot sample filled and were viable for analysis, 99% were correctly filled in Uganda and 53.4% in Cameroon. Reported ease of method performance (aOR: 24.77 95% CI 2.97-206.42, p = 0.003) and reduced collection time (aOR: 3.73 95% CI 1.26-11.04, p = 0.017) were associated with greater odds of PSC acceptance. HBsAg + and anti-HCV + prevalence were 11.1% and 1.0%, respectively. Conclusions In spite of country differences, overall, the PSC was reported as a feasible and acceptable viral hepatitis testing method. Acceptability and feasibility of the method must be explored in heterogeneous target communities and qualitative research to better understand country-specific barriers and facilitators should be carried out.